Management accounting - Mowen, Maryanne M. (Thomson/South-Western, 2006)
Management accounting is one of the most important courses in the business curriculum. From manufacturing to service, and every industry in between, management accounting infomation is used to help managers identify important issues, solve problems, and evaluate performance